1H NMR‐based metabolic investigation of the effect of Lentinula edodes‐derived polysaccharides on aged mice. Issue 3 (9th March 2017) - Xiaofei, Xu; Jiguo, Yang; Zhengxiang, Ning; Xuewu, Zhang
Abstract: Few comprehensive metabolic profiles of Lentinula edodes ‐derived polysaccharides on mammalians have been reported to date. In previous studies, a novel heteropolysaccharide, named L2, obtained from L. edodes had shown anti‐ageing effects in mice. In this study, a 1 H NMR‐based metabolomics approach was used to investigate the urinary metabolome changes in aged mice gavaged with L2 for better understanding of anti‐ageing mechanism. Six metabolites in urine were identified as potential markers for L2 treatment. An increase in α‐oxoglutarate (α‐OG) and a decrease in β‐hydroxybutyrate, glutamate, glucose, choline, and lactate were observed. Enrichment pathway analysis indicated that 11 metabolic pathways were disrupted after L2 treatment. These altered metabolic pathways are mainly associated with energy metabolism, amino acid metabolism, and glycolysis. The results suggest that L2 could exert anti‐ageing effects partly by regulating these pathways. Moreover, these findings may help better understand the mechanisms of the bioactivities of L. edodes ‐derived polysaccharides. Practical applications: In this study, a 1 H NMR‐based metabolomics approach was used to investigate the urinary metabolome changes in aged mice gavaged with a novel heteropolysaccharide L2 from Lentinula edodes . The findings may help better understand the mechanisms of bioactivities of L. edodes ‐derived polysaccharides, and used for further development of L2 in food and medicine.